The kids's table: A comprehensive assessment of the legal basis and implications of the "Filipino-style" party-list system of proportional representation - Pilapil, Rene G., Jr. (Animo Repository, 2014)
As a result of heated deliberations regarding the need for better representation of marginalized sectors, the framers of the 1987 Constitution came up with Article VI, Section 5 (1) and (2), otherwise known as the party-list provision. The party-list is an example of an electoral system of proportional representation; thus, it attempts to undo the unfairness of “winner-take-all” plurality systems by establishing a close link between votes won and seats gained. It is not a form of reserved seating for sectors, nor does it create exclusive constituencies for certain groups. It is merely an alternative manner distributing seats in proportion to the vote shares, and is widely recognized as providing more representation by giving a chance to more parties. However, despite this clear and distinct nature of the party-list, its implementation in the Philippine setting has led to an entirely different system altogether. As a result of the loose and vague language of Republic Act 7941, the interpretation of party-list law in subsequent jurisprudence gave birth to the “Filipino-Style” party-list system. In the four cases of Veterans, Ang Bagong Bayani, BANAT and Atong Paglaum, the Supreme Court has chosen to support the advocacy of marginalized groups in claiming that the party- list system belongs only to the latter. Due to the resulting policy, major political parties have been banned for most of the system’s existence, and its nature as a system of proportional representation was utterly nullified. Based on the reasoning of the Court, the Filipino-Style System is a mixture of functional representation and electoral system quotas, as it limits representation to certain groups in society. It is also a unique electoral system which focuses more on awarding seats to the most parties, with a distribution method that makes proportionality impossible. In short, the Filipino-Style System is not a party-list, and is thus against the plain language of the 1987 Constitution. More than being unconstitutional, however, the Filipino-Style System is also detrimental to the interests of the very same groups that it ostensibly seeks to protect. By focusing on the theory that representatives should resemble the represented, the system falls into numerous absurdities, and creates countless opportunities for legal controversy. By requiring major parties to organize separate sectoral wings in order to participate, it has severely weakened the chances of marginalized groups by dividing their constituencies and vote base. Worst of all, it has created an awareness that such a meager portion of the House of Representatives is the only place where the marginalized and underrepresented belong; not in the rest of government where they can truly advocate and champion their interests. It is thus a system which destroys the same principle that it seeks to uphold, and betrays the goal of social justice enshrined in the 1987 Constitution.